2020
DOI: 10.1111/jocd.13491
|View full text |Cite
|
Sign up to set email alerts
|

The six different injection techniques for the temple relevant for soft tissue filler augmentation procedures – Clinical anatomy and danger zones

Abstract: Objective The most promising facial region for inducing pan‐facial effects is the temporal region. The temple displays signs of facial aging itself which include temporal volume loss and increased visibility of the temporal crest, the temporal vasculature, the lateral orbital rim, and the upper zygomatic arch. The objective of this article is to provide a detailed review of temple anatomy pertaining to routinely performed temporal injection techniques, their expected esthetic outcomes as well as the intendant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 19 publications
0
69
0
Order By: Relevance
“…Another technique described by Coimbra and colleagues 5 administers soft tissue fillers via multiple smaller boluses around the anterior and superior aspect of the auricle purported to yield similar results. Despite the retrospective analysis of a large sample of 165 participants, the authors did not provide objective and reliable evidence for their claims, leaving the study unfortunately in the realm of subjective anecdotal outcome reports.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Another technique described by Coimbra and colleagues 5 administers soft tissue fillers via multiple smaller boluses around the anterior and superior aspect of the auricle purported to yield similar results. Despite the retrospective analysis of a large sample of 165 participants, the authors did not provide objective and reliable evidence for their claims, leaving the study unfortunately in the realm of subjective anecdotal outcome reports.…”
Section: Discussionmentioning
confidence: 96%
“…Despite the retrospective analysis of a large sample of 165 participants, the authors did not provide objective and reliable evidence for their claims, leaving the study unfortunately in the realm of subjective anecdotal outcome reports. The first study however to report on the temporal lifting technique (as presented here) by Suwanchinda and colleagues 4,5 investigated the injection‐related outcome of 15 Asian patients and combined their results with skin vector displacement analyses of three Caucasian body donors. Their study reported convincing objective outcome measures for their (clinical) injection‐related outcome, but their 3D analyses were performed in a different sample.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations